MAPPING HUMAN RESOURCE INDICATORS IN HOSPITAL RESEARCH : A BIBLIOMETRIC PERSPECTIVE - Solichati Fatonah; Qurratul Aini (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2026)
Human resource indicators are important determinants of hospital service quality because workforce management directly affects patient care and organizational performance. However, the literature on hospital human resource management remains fragmented, particularly regarding its relationship with service quality and performance outcomes. This study aimed to map the research landscape on human resource indicators in hospitals from a bibliometric perspective. A bibliometric analysis was conducted using the Scopus database for articles published between 2015 and 2025. Of 3,995 records initially identified, 1,985 articles met the eligibility criteria and were included in the final analysis. Bibliometric mapping was performed using VOSviewer. The results showed a clear increase in publication output over time, especially in 2024–2025, indicating growing scholarly interest in hospital human resource indicators. The keyword health care quality had the highest total link strength, showing that the literature is strongly oriented toward quality assessment, organizational performance, and service improvement. Overall, the findings demonstrate that research on hospital human resource indicators is closely linked to hospital quality, management, and patient safety, while several workforce-related themes remain underexplored.